DAP to gain if Khalid leaves: OPPORTUNITY: Religious scandals might give DAP a reason to boot Khalid, say experts - Ariff, Syed Umar (New Straits Times, 2014)
THE mission to oust Tan Sri Abdul Khalid Ibrahim as Selangor menteri besar is likely to receive a boost from DAP, but that support hinges on the out come of several ongoing religious issues in the state.